Implementasi Kebijakan Pajak Progresif Bagi Kendaraan Bermotor di Kantor Samsat Kota Denpasar - Ni Ketut Mentari Putri; I Gede Agus Wibawa (Universitas Warmadewa, 2023)
Local taxes are an important revenue or income for the Provincial Government of Bali. One of them is Motor Vehicle Tax (PKB). Along with the implementation of progressive taxes, the average tax rate is low, the lack of data related to the tax base, inaccurate assessments, and tax evasion committed by taxpayers. In this regard, this study aims to analyze the implementation of the progressive tax policy for motorized vehicles at the Denpasar City Samsat Office and the factors that influence the implementation of this progressive tax policy. The research method used is a qualitative descriptive approach with the technique of determining informants through purposive sampling. Data collection through observation, interviews, and literature study. Based on qualitative data analysis techniques, this study shows that the implementation of the Progressive Tax for Motorized Vehicles policy at UPT Samsat City of Denpasar has been going well but not yet optimal. This can be seen from the communication that has been going well but the transmission of communication has not been optimal, the availability of adequate resources, the disposition of tax officers who are quite good, and the existing bureaucratic structure. This is at the same time a supporting factor for the implementation process, while the inhibiting factors are communication transmission, taxpayer awareness, and the tax data collection application system which needs to be updated in order to achieve effective and efficient performance.